Structural and Optical Properties of Cobalt-Doped Zinc Oxide Thin Films Prepared By Spray Pyrolysis Technique (Baghdad Science Journal, 2025)
Undoped and Co-doped zinc oxide (CZO) thin films have been prepared by spray pyrolysis technique using solution of zinc acetate and cobalt chloride. The effect of Co dopants on structural and optical properties has been investigated. The films were found to exhibit maximum transmittance (~90%) and low absorbance. The structural properties of the deposited films were examined by x-ray diffraction (XRD). These films, deposited on glass substrates at (400? C), have a polycrystalline texture with a wurtzite hexagonal structure, and the grain size was decreased with increasing Co concentration, and no change was observed in lattice constants while the optical band gap decreased from (3.18-3.02) eV for direct allowed transition. Other parameters such as Texture Coefficient (Tc), dislocation density (?) and number of crystals (M) were also calculated .